2016
DOI: 10.3897/jhr.50.8173
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behavior and Preferences for Alternative Supplementary Feeds by the African Weaver Ant, Oecophylla longinoda Latreille (Hymenoptera, Formicidae)

Abstract: Weaver ants, Oecophylla spp, are effective predators that control a wide range of insect pests in multiple crops when maintained at high population. Supplementary feeding, particularly during reduced food availability is one of the management practices that maintain and boost weaver ants' populations. Experiments were conducted between September and October 2013, January and February, 2014 to determine the type of food preferred by weaver ants, O. longinoda. Twenty colonies of O. longinoda were provided with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Furthermore, we observed the weaver ants had difficulty to collect and remove milk powder using their mandibles. Nene et al (2016) explained that O. longinoda faced difficulty in collecting small particles back to their nest due to large mandibles. The current study showed O. smaragdina preferred tuna and chicken skin which had a high nutrient combination of protein and lipid contents, but they were not interested in milk powder which contains 2:1:1 ratio of carbohydrate, protein, and lipid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we observed the weaver ants had difficulty to collect and remove milk powder using their mandibles. Nene et al (2016) explained that O. longinoda faced difficulty in collecting small particles back to their nest due to large mandibles. The current study showed O. smaragdina preferred tuna and chicken skin which had a high nutrient combination of protein and lipid contents, but they were not interested in milk powder which contains 2:1:1 ratio of carbohydrate, protein, and lipid.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of O. smaragdina in Malaysia is abundant (Jander & Jander 1979;Blüthgen & Fiedler 2002), but little is known about their foraging activities (Peng et al 2012a) and food preferences (Nene et al 2016), particularly in this region. However, there are some researches on their colony structures (Offenberg et al 2012;Marcela et al 2012), ecology (Offenberg et al 2004), predation behaviours (Pierre & Idris 2013;Gathalkar & Barsagade 2016), their benefit as biological control agent (Offenberg et al 2013;Rodríguez-Gironés et al 2013), and nuisances caused by this species (Van Mele et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the research results, the humidity in the environment ranges from 60-65%. This makes it an ideal place for weaver ants to live and breed [19]. In addition, the light intensity needed to support the existence of weaver ants is 315-4550 lux.…”
Section: Environmental Factors Affecting the Presence Of Weaver Ants ...mentioning
confidence: 99%
“…The arrangement of these layers can be several rows beginning from the base tree trunks to expand further by several successive waves creating a few lines of defense (Lim, 2007). Other important aspects of effective foraging are the food quality and quantity alongside the strategies of the foragers such as secluded, tandem running, tandem carrying, group and mass foraging (Guénard & Silverman, 2011;Nene et al, 2016).…”
Section: Introductionmentioning
confidence: 99%